More microinvasive foci in larger tumours of breast ductal carcinoma in situ - Xiao-Yang Chen; Aye Aye Thike; Johnathan Xiande Lim; Boon Huat Bay; Puay Hoon Tan (Singapore Medical Journal)
Introduction: Microinvasion (Mi) is often thought to be an interim stage between ductal carcinoma in situ (DCIS) and invasive ductal carcinoma. This study aimed to investigate the potential influence of Mi on survival and assess its correlations with clinicopathological parameters, prognosis and molecular markers. Methods: The number of Mi foci in a cohort of 66 DCIS-Mi cases was assessed from haematoxylin and eosin–stained sections. Disease-free survival, clinicopathological parameters and biomarker expression were correlated with the number of Mi foci. Results: Higher numbers of Mi foci were found in larger tumours (P = 0.031). Conclusion: Greater extent of DCIS is associated with multifocal Mi.